The Protective Effects of p-Coumaric Acid on Acute Liver and Kidney Damages Induced by Cisplatin - Ekinci Akdemir, Fazile Nur (Biomedicines, 2017)
In this study, we aimed to investigate the effects of p-Coumaric acid (PCA) on cisplatin (CIS)-induced hepatotoxicity and nephrotoxicity in Wistar adult rats for 24 h compared to untreated control groups. In this experiment, 40 Wistar adult rats were utilized and divided randomly into five groups. After 24 h of CIS administration, liver and kidneys were harvested and assessed by H&E staining. Also, markers for oxidative stress and antioxidants were analyzed in theses tissues. Compared to the control group, accumulation of malondialdehyde was increased in groups treated CIS, whereas superoxide dismutase activities and glutathione levels were distinctly diminished in this group. The study’s histopathological findings such as hydropic degeneration, vascular congestion, sinusoidal dilatation in hepatocytes and tubular necrosis in kidneys were in accordance with the results of markers for oxidative stress. PCA may prevent hepatotoxicity and nephrotoxicity by increased antioxidant enzymes and reduced oxidant parameters.